A single crystal process window for electron beam powder bed fusion additive manufacturing of a CMSX-4 type Ni-based superalloy - Pistor, Julian; Breuning, Christoph; Körner, Carolin (Materials, 2021)
Using suitable scanning strategies, even single crystals can emerge from powder during additive manufacturing. In this paper, a full microstructure map for additive manufacturing of technical single crystals is presented using the conventional single crystal Ni-based superalloy CMSX-4. The correlation between process parameters, melt pool size and shape, as well as single crystal fraction, is investigated through a high number of experiments supported by numerical simulations. Based on these results, a strategy for the fabrication of high fraction single crystals in powder bed fusion additive manufacturing is deduced.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Electron beam melting; Grain selection; Microstructure; Ni-based superalloy; Single crystal